Inhibitory effect of Sinapic acid derivatives targeting structural and non-structural proteins of dengue virus serotype 2 An in-silico assessment - Roney, Miah; Dubey, Amit; Normaiza, Zamri; Mohd Fadhlizil Fasihi, Mohd Aluwi (Elsevier B.V., 2023)
DENV infects 50–100 million individuals, and 500,000 of them go on to acquire the more serious dengue hemorrhagic fever, which causes around 20,000 fatalities every year. Despite its widespread nature, there is no medication licenced to treat this condition. The purpose of this work is to identify anti-DENV medicines from sinapic acid (SA) derivatives utilising in-silico evaluation through docking and pharmacokinetics investigations. For the DENV-2 envelop protein, 1-O-β-d-glucopyranosyl sinapate had a significant docking score of −7.7 kcal/mol, while sinapoyl malate had a docking score of −6.7 kcal/mol for the DENV-2 NS2B/NS3 protein. Additionally, according to the PASS server, 1-O-β-d-glucopyranosyl sinapate and sinapoyl malate have a wide range of enzymatic activities since their probability active (Pa) values is > 0.700. These compounds exhibit a numerous pharmacological effect through activating the body's enzymes, according to analyses of their pharmacokinetic qualities. Accordingly, these substances showed acute toxicity rates at LD50 log10 (mmol/g) and LD50 (mg/g) concentrations when administered via various routes, including intraperitoneal, intravenous, oral, and subcutaneous. The result of this research suggests, 1-O-β-d-glucopyranosyl sinapate and sinapoyl malate may function as possible inhibitors to halt the DENV, and more in-vitro and in-vivo research is required to validate their activity and other features.